On Scales, Salience & Referential Language Use (A Revisit) - Franke, Michael (Proceedings of the Amsterdam Colloquium, 2011)
Kennedy (2007) explains differences in the contextual variability of gradable adjectives in terms of salience of minimal or maximal degree values on the scales that these terms are associated with in formal semantics. In contrast, this paper suggests that the attested contextual variability is a consequence of a more general tendency to use gradable terms to preferentially pick out extreme-valued properties. This tendency, in turn, can be explained by demonstrating that it is pragmatically beneficial to use those gradable properties in referential descriptions that are perceptually salient in a given context.